CRASH PROGRAM JALUR KRITIS DENGAN CARA OVERLAPPING (STUDY REVIEW) - Irwan, Hery (Fakultas Teknik, Universitas Riau Kepulauan, 2019)
Project management in the length of time of completion or better known as lead time is the time that has been agreed between the project implementers in this project managers and customers as the owner of the project. Time-based project implementers will make planning, scheduling and control of existing resources with the purpose of the length of the project in accordance with the agreed upon. In the process constraints will always occur which cause the delay activities that become part of the overall project. The delay that occurs on the critical path if not controlling and acceleration would cause backwards in time from the time of completion of the project. This will cause losses for both the executor fines for the delay as well as for the project owner to lose an opportunity of reception of the project late from agreements. This paper contains the possibility of doing a program crash or the acceleration by means of melaukukan overlapping. For sure the acceleration by means of overlapping could not immediately be implemented in all activities of the project. The decision to do overlapping largely determined by the knowledge and experience of the person in charge of the project. Â Keywords: Crash program, overlapping, critical path method.